Identifying sexual abuse in same-sex relationships: turning points and meta-narratives - Øverlien, Carolina (Journal of family violence, 2024)
Purpose: Youth intimate partner violence (YIPV) is an under-researched topic within the field of domestic violence. This is particularly true of same-sex YIPV. In this article, the words of one young man, Philip, are analyzed to explore how he narrates his process of defining his sexual experiences as abuse and, consequently, himself as a possible victim of IPV. Methods: The qualitative in-depth interview with Philip was conducted as part of a larger study on YIPV in Norway, with a specific focus on sexual YIPV. The article is framed both theoretically and methodologically by the assumption that narratives give meaning to our experiences. Meta-narratives and turning points are used as tools for narrative analysis. Results: Important contextual issues in Philip’s storyline include his prior exposure to severe homophobic bullying, being forced to return to the closet as his partner had not yet come out, and no prior experience of serious romantic relationship. Influential cultural meta-narratives regarding IPV and gender that complicate his process of identifying his experiences as abuse include the violence of adult men towards adult women, the ever-present male sex drive, and the importance of physical violence and bodily size and strength. The findings are discussed in light of the theory of the ideal victim. Conclusion: Schools need to include sexual minority youth when teaching about sex and relationships, and professionals working with youth need to actively ask them about experiences of violence and abuse in their relationships, regardless of their sexuality.